Histological Study on Optic Tectum in Hemida ctylus Flaviviridis - Hussien, A. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A histological study was conducted to examine the structure of optic tectum in Hemidactylus flaviviridis. The results showed that the optic tectum consists of fourteen strata organized in three zones. The deep zone which extends from the first stratum (around optic ventricle) to the fifth stratum. The medium zone comprises the sixth & seventh strata, which represent the center of optic tectum. The superficial zone which extends from the eighth stratum to the fourteenth stratum and forms the retino recipient region.         The strata of deep zone are called the Stratum Griseum et Periventricular ( SGAP ) , the sixth stratum  is  called the Stratum Album Central ( SAC ) and  the seventh stratum is   called the Stratum Griseum Central ( SGC) . The strata of superficial zone are called  the Stratum Album Griseum Superficial ( SAGS) except the fourteenth stratum which is called the Stratum Opticum (SO ).